Production of borneol, camphor, and bornyl acetate using engineered Saccharomyces cerevisiae - Masahiro Tominaga; Kazuma Kawakami; Hiro Ogawa; Tomomi Nakamura; Akihiko Kondo; Jun Ishii (Metabolic Engineering Communications)
Microbial production of bicyclic monoterpenes is of great interest because their production primarily utilizes non-sustainable resources. Here, we report an engineered Saccharomyces cerevisiae yeast that produces bicyclic monoterpenes, including borneol, camphor, and bornyl acetate. The engineered yeast expresses a bornyl pyrophosphatase synthase from Salvia officinalis fused with mutated farnesyl pyrophosphate synthase from S. cerevisiae and two mevalonate pathway enzymes (an acetoacetyl-CoA thiolase/hydroxymethylglutaryl-CoA [HMG-CoA] reductase and an HMG-CoA synthase) from Enterococcus faecalis. The yeast produced up to 23.0 mg/L of borneol in shake-flask fermentation. By additionally expressing borneol dehydrogenase from Pseudomonas sp. TCU-HL1 or bornyl acetyltransferase from Wurfbainia villosa, the engineered yeast produced 23.5 mg/L of camphor and 21.1 mg/L of bornyl acetate, respectively. This is the first report of heterologous production of camphor and bornyl acetate.